Taste and Smell Function in Head and Neck Cancer Survivors. (29th May 2021) - Alfaro, Raul; Crowder, Sylvia; Sarma, Kalika P; Arthur, Anna E; Pepino, Marta Yanina
Abstract: Survivors of head and neck squamous cell cancers (HNSCC) frequently complain of taste dysfunction long after radiation therapy is completed, which contradicts findings from most sensory evaluation studies that predict dysfunction should resolve few months after treatment. Therefore, it remains unclear whether taste and smell function fully recovers in HNSCC survivors. We evaluated HNSCC survivors ( n = 40; age 63 ± 12 years, mean ± standard deviation) who received radiation therapy between 6 months and 10 years before recruitment and compared their responses to those of a healthy control group ( n = 20) equivalent in age, sex, race, smoking history, and body mass index. We assessed regional (tongue tip) and whole-mouth taste intensity perception using the general Labeled Magnitude Scale and smell function using the University of Pennsylvania Smell Identification Test (UPSIT). To determine possible differences between groups in retronasal smell perception, we used solutions of sucrose with strawberry extract, citric acid with lemon extract, sodium chloride in vegetable broth, and caffeine in coffee and asked participants to rate perceived smell and taste intensities with and without nose clips. We found groups had similar UPSIT and taste intensity scores when solutions were experienced in the whole mouth. However, HNSCC survivors were less likely to identify low concentrations of bitter, sweet, or salty stimuli in the tongue tip relative to healthy controls. Our findings suggest persistent and subtle localized damage to the chorda tympani or to the taste buds in the fungiform papillae of HNSCC survivors, which could explain their sensory complaints long after completion of radiotherapy.